Microbial Communities of the Hydrothermal Scaly-Foot Snails From Kairei and Longqi Vent Fields - Bai, Shijie; Xu, Hengchao; Peng, Xiaotong (Frontiers in Marine Science, 2021)
The microbial communities of the hydrothermal Scaly-foot Snails (SFSs) from independent hydrothermal vent fields have not been investigated in depth. In this study, we collected SFSs from two different hydrothermal environments located on the Central Indian Ridge (CIR) and the Southwest Indian Ridge (SWIR), the Kairei and Longqi vent fields, respectively. Additionally, one SFS collected from the Kairei vent field was reared for 16 days with in situ deep-sea seawater. The epibiotic and internal samples of SFSs, including ctenidium, esophageal gland, visceral mass, shells, and scales, were examined for microbial community compositions based on the 16S rRNA gene. Our results revealed significant differences in microbial community composition between SFSs samples collected from Kairei and Longqi vent fields. Moreover, the microbial communities of epibiotic and internal SFS samples also exhibited significant differences. Epibiotic SFS samples were dominated by the bacterial lineages of Sulfurovaceae, Desulfobulbaceae, Flavobacteriaceae, and Campylobacteraceae. While in the internal SFS samples, the genus Candidatus Thiobios, affiliated with the Chromatiaceae, was the most dominant bacterial lineage. Furthermore, the core microbial communities of all samples, which accounted for 78 ∼ 92% of sequences, were dominated by Chromatiaceae (27 ∼ 49%), Sulfurovaceae (10 ∼ 35%), Desulfobulbaceae (2 ∼ 7%), and Flavobacteriaceae (3 ∼ 7%) at the family level. Based on the results of random forest analysis, we also found the genera Desulfobulbus and Sulfurovum were the primary bacterial lineages responsible for the dissimilarity of microbial communities between the SFS samples collected from the Kairei and Longqi vent fields. Our results indicated that the microbial lineages involved in the sulfur cycle were the key microorganisms, playing a crucial role in the hydrothermal vent ecosystems. Our findings expand current knowledge on microbial diversity and composition in the epibiotic and internal microbial communities of SFS collected from different hydrothermal vent fields.